Women and knowledge in early Christianity - Tervahauta, Ulla. (Vigiliae Christianae, Supplements, 2017)
Women and knowledge are interconnected in several ways in late ancient and early Christian discourses, not least because wisdom (Sophia) and spiritual knowledge (Gnosis) were frequently personified as female entities. Ancient texts deal with idealized women and use feminine imagery to describe the divine but they also debate women's access to and capacity of gaining knowledge. Combining rhetorical analysis with social historical approaches, the contributions in this book cover a wide array of source materials, drawing special attention to the so-called Gnostic texts. The fourteen essays, written by prominent experts of ancient Christianity, are dedicated to Professor Antti Marjanen (University of Helsinki).